Causes of Death in Implant Patients Treated in the Edentulous Jaw: A Comparison between 2098 Deceased Patients and the Swedish National Cause of Death Register - Jan Kowar; Victoria Stenport; Mats Nilsson; Torsten Jemt (Hindawi Limited, 2019)
Background. Previous research has reported an association between tooth loss and patient mortality, while the cause of death has not been elucidated. Objective. The purpose was to describe and compare the cause of death in implant patients treated consecutively in the edentulous arch with a reference population. Methods. Altogether, 3902 patients were included between 1986 and 2014. Data on the causes of death for deceased patients were compared to the Swedish National Cause of Death Register for a comparable time period. Standardised mortality ratios (SMRs) were calculated based on gender and age and tested for statistical significance. Results. Most deceased patients (2,098) died from diseases in the circulatory system (CVD; 42%) and from cancers (26%). SMR indicated a generally increased mortality (total group) compared to the reference population during inclusion (P<0.05; 1986-2014). Patients treated early (1986-1996) showed a lower SMR compared to patients treated later (P<0.05; 1997-2014) especially related to CVDs. Younger patients (<60 years at surgery) showed an increased mortality due to CVDs when treated late (1997-2014; SMR = 5.4, P<0.05). Elderly patients (>79 years at surgery) showed a significantly lower mortality in almost all observed causes of death (1986-2014; P<0.05) with also a significantly lower mortality due to CVDs during the early period (1986-1996; SMR = 0.3, P<0.05). Conclusion. An overall increased mortality was observed for the edentulous implant patient compared to the reference population. Elderly patients (>79 years) showed significantly lower mortality for all causes of death independent of the time period of implant surgery. Younger patients (<60 years) present an increased risk for early mortality related to CVD. SMR for all causes of death increased for patients treated late (1997-2014) as compared to patients treated early (1986-1996).